Death in Venice - Reed, Terence James (Twayne Publishers, 1994)
Provides in-depth analysis of the literary work Death in Venice, as well as its importance and critical reception. Includes a chronology of the life and works of the author
Description based on print version record
Keywords: Mann; Thomas; Tod in Venedig